Identifying Key Somatic Copy Number Alterations Driving Dysregulation of Cancer Hallmarks in Lower-Grade Glioma - Zhou, Yao; Wang, Shuai; Yan, Haoteng; Pang, Bo; Zhang, Xinxin; Pang, Lin; Wang, Yihan; Xu, Jinyuan; Hu, Jing; Lan, Yujia; Ping, Yanyan (Frontiers in Genetics, 2021)
Somatic copy-number alterations (SCNAs) were major contributors to cancer development, which were pervasive and highly heterogeneous in human cancers. However, the driver roles of SCNAs in cancer were insufficiently characterized. We combined network propagation and linear regression models to design an integrative strategy to identify driver SCNAs and dissect the functional roles of SCNAs by integrating profiles of copy number and gene expression in LGG. We applied our strategy to 511 lower-grade glioma (LGG) patients and identified 98 driver genes which dysfunctioned 29 dysregulation cancer hallmark signatures, forming 143 active gene-hallmark pairs. We found that these active gene-hallmark pairs could stratify LGG patients into four subtypes with significantly different survival times. Two new subtypes with similar poor prognosis were driven by two gene sets (one including EGFR,CDKN2A,CDKN2B,INFA8,INFA5 and the other including CDK4,AVIL,DTX3) respectively. The SCNAs of the two gene set showed significant mutually-exclusive manner, but they could dysregulate same cancer hallmark (including E2F_TARGETS and G2M_CHECKPOINT)Compared with previous methods, our strategy could not only capture the known cancer genes and directly dissect the functional roles of their SCNAs in LGG, but also discovered the functions of new driver genes in LGG, such as IFNA5,IFNA8, DTX3. Additionally, our method can be applied to a variety of cancer types to explore the pathogenesis of driver SCNAs and improve the treatment and diagnosis of cancer.